(untitled) (MAUSAM, 2014)
During the afternoon of 5th April, 2010, a thunderstorm swept across Guwahati Airport (Lat. 26º26´, Long 91º35´) and neighborhood from northwest direction. Strong squally winds (reaching up to 49 knots) and high intensity rain (11mm in 15 minutes) were registered accompanying the storm. One person was killed by the falling tree due to squally winds and several others were injured by the event. The observed evolution of temperature, humidity, wind and pressure at Guwahati Airport, as well as the sequence of satellite and radar images, revealed the presence and movement of convective cells. An observational analysis of the event has been given in this paper. The aim of the study is to contribute to the characterization of these events by analyzing the observational information available. The diagnosis is aimed at helping forecasters to identify this kind of organized deep convective events and being able to issue timely warnings. The synoptic scenario shows warm and moist advection from the Bay of Bengal in low levels over Northeastern region of India and an upper-level north-south trough running from Sub-Himalayan West Bengal to north Orissa. This situation is known to be favorable for development of severe convection over Northeastern region of India during pre-monsoon season.